Growth Response of Robusta Cooffe Seedling (Coffea Robusta L.) on Planting Media Composition and Watering Interval - Rejchi Perdana Situmorang; Asil Barus; Chairani Hanum (Universitas Sumatera Utara, 2018)
Growth Response of Robusta Cooffe Seedling (Coffea Robusta L.) on Planting Media Composition and Watering Interval